The Speech Act of Complaint: Socio-Cultural Competence Used by Native Speakers of English and Indonesian - Kaharuddin; Hasyim, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Complaining is frequently regarded as a negative act stated to attack a person who is responsible for a wrong behavior. However, the proper use of complaints can improve an offensive situation and establish solidarity between interlocutors. This study is aimed at comparing the strategies of complaints made by college-educated native speakers of English and Indonesian. Qualitative method was used to carry out this study by involving 14 English native speakers (ENSs) and 30 Indonesian native speakers (INSs) who were randomly selected. Survey questions were used to collect the data. The survey questions contained three offenses on complaint of friends, intimates, and strangers which were given to identify complaint strategies used by the respondents. The results of the data analysis show that ENSs and INSs used a varied of complaint strategies. For situation one: a friend makes a big mess in the kitchen, most ENSs employed implicit strategy (reproach and annoyance) whereas INSs primarily used implicit strategy (reproach, annoyance, and silence). In situation two: a child bumps into his parent, most ENSs used implicit (reproach and annoyance) and explicit strategy (explicit complaint) whereas INSs frequently did explicit strategy (explicit complaint). For situation three: a driver runs his car into the side of one’s car, ENSs mainly employed explicit strategy (explicit complaint and accusation) whereas most INSs used explicit strategy (explicit complaint, accusation, and threat). We believe that the findings from this study can be used as socio-cultural knowledge by non-native speakers of English and Indonesian for developing their sociocultural competence in cross-cultural communications.